African head and neck fellowships: A model for a sustainable impact on head and neck cancer care in developing countries. Issue 6 (16th January 2019) - Fagan, Johannes J.; Otiti, Jeffrey; Aswani, Joyce; Konney, Anna; Diom, Evelyne S.; Baidoo, Kenneth; Onakoya, Paul A.; Mugabo, Rajab M.; Noah, Patrick; Mashamba, Victor; Kundiona, Innocent; Garba, Mainasara; et al.
Abstract: Background: There is an extreme shortage of head and neck surgeons in Africa. Fourteen head and neck surgeons have completed fellowships in Cape Town and Cameroon. This study determines whether such Africa‐based fellowships are a good model for developing countries by making a sustainable impact on head and neck cancer care. Methods: An observational study was conducted by emailing questionnaires to past fellows. Results: All fellows had returned to teaching hospitals in their counties. Seven established new multidisciplinary cancer teams. Head and neck operations had increased by >335%, as had complexity of the surgery. There was effective transfer of surgical skills to trainees. All considered head and neck fellowships to be the best model to grow head and neck care. Conclusion: Head and neck fellowships in developing countries are effective models for establishing training programs and for increasing provision of specialized surgical services in a sustainable fashion.